Analysis of Koo-Kleinstreuer-Li model water-based nanofluid: Interval Type 2 fuzzy approach - M.M. Nayak; S.R. Mishra; Rupa Baithalu (Partial Differential Equations in Applied Mathematics)
The current study investigates the role of conducting nanofluid past a thin layer that is positioned horizontally while addressing uncertainties in the system using interval type-2 trapezoidal fuzzy sets [IT2TrFS]. The flow phenomena enrich due to the consideration of Brownian conductivity based on the Koo–Kleinstreuer–Li (KKL) model thermal conductivity. The modeled problem for the nanofluid is transformed into ordinary by the utilization of similarity rules and a numerical technique is adapted for the solution. Interval type-2 trapezoidal fuzzy sets are used in this fuzzy analysis to investigate the role of several physical factors on velocity and temperature distribution, shear rate, Nusselt number (rate of heat transfer), nanoparticle diameter, fluid temperature, and volume concentration. The outcomes, which show these parameters affect the flow behavior, are displayed as tables and graphs. The main conclusions show that Brownian conductivity is strongly enhanced by fluid temperature and diminishes with increasing particle diameter. Furthermore, raising the volume concentration of nanoparticles tends to lower fluid temperature, which speeds up cooling procedures and is beneficial for the manufacturing of industrial materials.